Patient-reported impact of spondyloarthritis on work disability and working life: the ATLANTIS survey. Issue 1 (December 2016) - Ramonda, Roberta; Marchesoni, Antonio; Carletto, Antonio; Bianchi, Gerolamo; Cutolo, Maurizio; Ferraccioli, Gianfranco; Fusaro, Enrico; De Vita, Salvatore; Galeazzi, Mauro; Gerli, Roberto; Matucci-Cerinic, Marco; Minisola, Giovanni; et al.
Abstract Background The aim was to establish how patients experience the impact of spondyloarthritis (SpA) on work disability and working life. Methods The survey was performed in 17/20 regions in Italy (1 January to 31 March 2013). A multiple-choice questionnaire was published on the official website of the sponsor - the National Association of Rheumatic Patients (ANMAR) - and hard-copies were distributed at outpatient clinics for rheumatic patients. Results Respondents (n = 770) were of both sexes (56 % men), educated (62 % at high school or more), of working age (75 % aged ≤60 years), and affected by SpA. The most common types diagnosed were ankylosing spondylitis (AS) (39 %) and psoriatic arthritis (PsA) (36 %). Respondents were working full-time (45 %), part-time (8 %) or had retired (22 %); 15 % were unemployed (for reasons linked to the disease or for other reasons, students or housewives). Patients reported disability (39 %), were receiving disability benefits (34 %), were experiencing important limitations that were hindering their professional development/career (36 %) and some had to change/leave their job or lost it because of SpA (21 %). Employed respondents (n = 383) had worked on average 32.2 h in the last 7 days. More hours of work were lost over the last 7 days due to SpA (2.39 h vs 1.67 h). The indirect costs of the disease amounted to €106/week for patients reporting well-being/good physical conditions/improvement and €216/week for those reporting permanent impairment. Conclusions Most patients were in the midst of their productive years and were experiencing considerable difficulties in carrying out their job because of the disease: half of them reported disability and one third were experiencing important limitations in their career perspective.